1991
DOI: 10.1128/aem.57.7.2074-2078.1991
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Phosphorus Stimulation of Bacterioplankton Production in a Meso-Eutrophic Lake

Abstract: Experiments were conducted to determine whether production of heterotrophic bacterioplankton in a small meso-eutrophic lake was influenced by the dissolved inorganic phosphorus (DIP) supply. DIP may indirectly limit bacterial production by limiting phytoplankton, which in turn may limit the carbon available to bacteria. Direct DIP limitation of bacteria occurs where the availability of DIP for bacteria is insufficient to maintain growth. This work examined direct DIP limitation of bacteria by removing phytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 14 publications
8
34
0
Order By: Relevance
“…Inorganic P and N enrichments stimulated bacterioplankton specific activity in four of our five 6.0 treatments regardless of the presence or absence of phytoplankton activity (Figs lb,2a,b & c), indicating that inorganic P and N can directly limit bacterioplankton growth in our study lake. Such results are supported by recent reports of inorganic P stimulation of bacterioplankton growth in an oligotrophic lake (Coveney & Wetzel, 1992) and in a mesoeutrophic lake (Toolan et al, 1991). Our results, in concert with those of others, do not support the common view that the growth of bacterioplankton in nutrientdeficient lakes is always limited by the availability of reduced carbon substrates (Currie & Kaiff, 1984).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Inorganic P and N enrichments stimulated bacterioplankton specific activity in four of our five 6.0 treatments regardless of the presence or absence of phytoplankton activity (Figs lb,2a,b & c), indicating that inorganic P and N can directly limit bacterioplankton growth in our study lake. Such results are supported by recent reports of inorganic P stimulation of bacterioplankton growth in an oligotrophic lake (Coveney & Wetzel, 1992) and in a mesoeutrophic lake (Toolan et al, 1991). Our results, in concert with those of others, do not support the common view that the growth of bacterioplankton in nutrientdeficient lakes is always limited by the availability of reduced carbon substrates (Currie & Kaiff, 1984).…”
Section: Discussionsupporting
confidence: 56%
“…Such a relationship is supported by the positive correlations observed between bacterioplankton production and phytoplankton biomass (Fuhrman, Ammerman & Azam, 1980;Cole, Findlay & Pace, 1988;White et al, 1991). Recent studies have shown that bacterioplankton growth rates can be stimulated directly by inorganic P enrichment in both oligotrophic (Coveney & Wetzel, 1992) and mesotrophic lajfe water (Toolan, Wehr & Findlay, 1991). These reports are consistent with the fact that bacterioplankton inorganic P and N uptake systems have higher affinities for P and N than those of phytoplankton (Currie & Kalff, 1984;Currie, Bentzen & Kalf, 1986;Vadstein & Olsen, 1989).…”
Section: Introductionmentioning
confidence: 63%
“…Past studies indicate that P generally limits microbial growth in lakes (reviewed by Vadstein, 2000), including eutrophic lakes like Lake Mendota (Toolan et al, 1991). In our study, the SRP pool (often considered the most bioavailable fraction) was not exhausted and the APA [a proxy for P starvation (Jurgens et al, 1999)] changed little in each season following P amendment ( Fig.…”
Section: Phosphorus Dynamicssupporting
confidence: 46%
“…This feature remained unchanged from 1998 to 1999, although the sediment resuspension frequencies, spatial distributions and intensities of plumes between these 2 years were significantly different. The role of bacteria in freshwater ecosystems has received a great deal of attention in recent field measurements [Toolan et al, 1991;Coveney and Wetzel, 1992;Morris and Lewis, 1992;Cotner, 2000]. Moreover bacteria are important competitors with phytoplankton for dissolved inorganic phosphorus (DIP) [Currie and Kalff, 1984;Cotner and Wetzel, 1992;Vadstein et al, 1993].…”
Section: Discussionmentioning
confidence: 99%